Working with Roosevelt. - Rosenman, Samuel I. (New York Harper & Brothers, Publishers, 1952)
Samuel Rosenman worked with Governor and then President Franklin Delano Roosevelt for seventeen years as a speechwriter. He later wrote the introduction to the thirteen volumes of Public Papers and Addresses of Frank Roosevelt. . As Rosenman says: One measure of him (Roosevelt) as a President and as a man is what he said and wrote in his public life. More than any other president up to the time of this writing, Roosevelt used the spoken and written word to exercise leadership and to carry out policies. This book is essentially a story of his words, of the ideas behind them, and of their translation into policy and action. Bust since the words necessarily involve the man himself, this story must tell something of the sort of man Roosevelt was, the kind of leadership he furnished, the imprint he left on the national fabric and worked pattern. The story of his words involves also the men who helped him shape those words and ideas and policies. Finally, it is the story of the circumstances under which the words were written, what the President hoped to accomplish by them, and how far he was successful.
Index.
Keywords: Roosevelt, Franklin D. -- 1882-1945; History -- 20th century